2014
DOI: 10.4209/aaqr.2013.05.0178
|View full text |Cite
|
Sign up to set email alerts
|

ab initio Thermodynamic Study of the CO2 Capture Properties of M2CO3 (M = Na, K)- and CaCO3-Promoted MgO Sorbents Towards Forming Double Salts

Abstract: The CO 2 capture properties of M 2 CO 3 (M = Na, K)-promoted and CaCO 3 -promoted MgO sorbents are investigated by first-principles density functional theory complemented with lattice phonon calculations. The calculated thermodynamic properties indicate that by forming double salts (M 2 Mg(CO 3 ) 2 and CaMg(CO 3 ) 2 ), compared to pure MgO, the maximum allowable CO 2 capture temperatures of the M 2 CO 3 -and CaCO 3 -modified MgO sorbents are shifted to higher temperature ranges. Under pre-combustion conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 37 publications
(57 reference statements)
3
44
0
1
Order By: Relevance
“…The relatively higher concentration of available CO 2 dissolved in promoters may explain the faster initial kinetics at 275-325 °C than that at 350-375 °C in Fig. 8b; and 2) the enthalpy change of MgCO 3 formation (CO 2 +MgOĺMgCO 3 , ǻH 300K = -106 kJ• mol -1 ) is negative [44], thus thermodynamically, the conversion to MgCO 3 is inhibited and its decomposition is enhanced at higher temperatures. Taken together, the overall performance of a sorbent depends on the balance of these effects, and an optimal operating temperature exists for a promoted MgO.…”
Section: Effect Of Content Of Nano 3 /Nanomentioning
confidence: 96%
“…The relatively higher concentration of available CO 2 dissolved in promoters may explain the faster initial kinetics at 275-325 °C than that at 350-375 °C in Fig. 8b; and 2) the enthalpy change of MgCO 3 formation (CO 2 +MgOĺMgCO 3 , ǻH 300K = -106 kJ• mol -1 ) is negative [44], thus thermodynamically, the conversion to MgCO 3 is inhibited and its decomposition is enhanced at higher temperatures. Taken together, the overall performance of a sorbent depends on the balance of these effects, and an optimal operating temperature exists for a promoted MgO.…”
Section: Effect Of Content Of Nano 3 /Nanomentioning
confidence: 96%
“…Figure 5 shows the changes of MgO turnover temperatures by adding different oxides or carbonates. Generally, by mixing alkali metal oxides, M 2 O (M = Na, K, Cs, Ca) or their carbonates (M 2 CO 3 ) into MgO, the corresponding newly formed mixing systems have higher turnover temperatures, making them useful as CO 2 sorbents through the reaction MgO + CO 2 + M 2 CO 3 = M 2 Mg(CO 3 ) 2 (Zhang et al, 2013;Duan et al, 2014).…”
Section: T a >>T B And The A Component Is Key To Capturing Comentioning
confidence: 99%
“…Zhang et al 12 synthesized a Na-promoted double salt MgO sorbent, including NaNO 3 , for CO 2 capture in the syngas of a pre-combustion process. Duan et al 16 conducted a computational study of Na-, K-, and Ca-promoted MgO sorbents using density functional theory (DFT) and phonon dynamics. Yang et al 13 investigated the role of NaNO 3 in a Ca-promoted double salt and reported that NaNO 3 enhances the absorbent activity by facilitating ion diffusion.…”
Section: Introductionmentioning
confidence: 99%